Identification of patterns of factors preceding severe or life‐threatening asthma exacerbations in a nationwide study. Issue 5 (19th December 2017) - Tanaka, H.; Nakatani, E.; Fukutomi, Y.; Sekiya, K.; Kaneda, H.; Iikura, M.; Yoshida, M.; Takahashi, K.; Tomii, K.; Nishikawa, M.; Kaneko, N.; Sugino, Y.; et al.
Abstract: Background: Reducing near‐fatal asthma exacerbations is a critical problem in asthma management. Objectives: To determine patterns of factors preceding asthma exacerbations in a real‐world setting. Methods: In a nationwide prospective study of 190 patients who had experienced near‐fatal asthma exacerbation, cluster analysis was performed using asthma symptoms over the 2‐week period before admission. Results: Three distinct clusters of symptoms were defined employing the self‐reporting of a visual analogue scale. Cluster A (42.1%): rapid worsening within 7.4 hours from moderate attack to admission, young to middle‐aged patients with low Body mass index and tendency to depression who had stopped anti‐asthma medications, smoked, and hypersensitive to environmental triggers and furred pets. Cluster B (40.0%): fairly rapid worsening within 48 hours, mostly middle‐aged and older, relatively good inhaled corticosteroid (ICS) or ICS/long‐acting beta‐agonist (LABA) compliance, and low perception of dyspnea. Cluster C (17.9%): slow worsening over 10 days before admission, high perception of dyspnea, smokers, and chronic daily mild‐moderate symptoms. There were no differences in overuse of short‐acting beta‐agonists, baseline asthma severity, or outcomes after admission for patients in these 3 clusters. Conclusion: To reduce severe or life‐threatening asthma exacerbation, personalized asthma management plans should be considered for each cluster. Improvement of ICS and ICS/LABA compliance and cessation of smoking are important in cluster A. To compensate for low perception of dyspnea, asthma monitoring of peak expiratory flow rate and/or exhaled nitric oxide would be useful for patients in cluster B. Avoidance of environmental triggers, increase usual therapy, or new anti‐type 2 response‐targeted therapies should be considered for cluster C.